A new approach for the investigation of reperfusion-related brain injury. (25th October 2006) - Maier, C.M.; Hsieh, L.; Crandall, T.; Narasimhan, P.; Chan, P.H.
Abstract : Effective stroke therapies require recanalization of occluded cerebral blood vessels; however, early reperfusion can cause BBB (blood–brain barrier) injury, leading to cerebral oedema and/or devastating brain haemorrhage. These complications of early reperfusion, which result from excess production of ROS (reactive oxygen species), significantly limit the benefits of stroke therapies. Here, we summarize some of the findings that lead to the development of a novel animal model that facilitates identification of specific free radical-associated components of the reperfusion injury process and allows therapeutic interventions to be assessed. In this model, KO (knockout) mice containing 50% activity of the mitochondrial antioxidant manganese-SOD (superoxide dismutase) (SOD2-KO) undergo transient focal ischaemia followed by reperfusion. These animals have delayed (>24 h) BBB breakdown associated with activation of matrix metalloproteinase-9, inflammation and a high brain haemorrhage rate. These adverse consequences are absent from wild-type littermates, SOD2 overexpressors and minocycline-treated SOD2-KO animals. In addition, using microvessel isolations following in vivo ischaemia/reperfusion, we were able to show that the tight junction membrane protein, occludin, is an early and specific target in ROS-mediated microvascular injury. This new model is ideal for studying ischaemia/reperfusion-induced vascular injury and secondary brain damage and offers a unique opportunity to evaluate free radical-based neurovascular protective strategies.